2021
DOI: 10.3390/ijerph18062812
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Physical Exercise Programs for Older Adults in Latin America: A Systematic Review of Randomized Controlled Trials

Abstract: Aim: To characterize physical exercise programs for older adults in Latin America. Methods: This review was conducted in accordance with the PRISMA statement. A search for randomized controlled trials (RCTs) published between the years 2015 and 2020 was performed in the Scopus, MedLine and SciELO databases. Results: A total of 101 RCTs were included. A large percentage of the studies had an unclear risk of bias in the items: selection, performance, detection and attribution. Furthermore, a heterogeneous level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 124 publications
0
8
0
Order By: Relevance
“…To date, the few examples found using the GUIDED checklist include two peer-reviewed articles reporting interventions aimed at improving mental health help-seeking behaviors for male students [ 73 ] and anxiety and depression management in patients with chronic obstructive pulmonary disease (COPD) [ 74 ], two pre-prints reporting interventions aimed to improve early diagnosis of cancer in primary care [ 75 ] and targeting antipsychotic prescription to nursing home residents with dementia [ 76 ], and one doctoral thesis reporting an arts-based intervention for patients with kidney disease [ 77 ]. However, some researchers have used the Consensus on Exercise Reporting Template (CERT) [ 78 ] to characterize physical activity programs for older adults in Latin America [ 36 ] and assess the feasibility of an enhanced prescribed exercise program in older acute medical patients [ 79 ] and the effectiveness of falls prevention interventions on reducing falls in hospitalized adults [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the few examples found using the GUIDED checklist include two peer-reviewed articles reporting interventions aimed at improving mental health help-seeking behaviors for male students [ 73 ] and anxiety and depression management in patients with chronic obstructive pulmonary disease (COPD) [ 74 ], two pre-prints reporting interventions aimed to improve early diagnosis of cancer in primary care [ 75 ] and targeting antipsychotic prescription to nursing home residents with dementia [ 76 ], and one doctoral thesis reporting an arts-based intervention for patients with kidney disease [ 77 ]. However, some researchers have used the Consensus on Exercise Reporting Template (CERT) [ 78 ] to characterize physical activity programs for older adults in Latin America [ 36 ] and assess the feasibility of an enhanced prescribed exercise program in older acute medical patients [ 79 ] and the effectiveness of falls prevention interventions on reducing falls in hospitalized adults [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…This framework is appropriate to be applied in those interventions including a number of components interacting with each other, several recipients and outcomes, different skills needed by the facilitators and a certain level of tailoring. During the intervention development process, decisions were taken in accordance with evidence from similar interventions and results from our previous studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 62 ]. We also integrated the recommendations of a working group, the appropriateness of different frameworks used in implementation research, and evidence shown by few strategies which seemed to be effective.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the few examples found using the GUIDED checklist includes two peer-reviewed articles reporting interventions aimed to improve mental health help-seeking behaviours for male students [73], and anxiety and depression management in patients with chronic obstructive pulmonary disease (COPD) [74]; two pre-prints reporting interventions aimed to improve early diagnosis of cancer in primary care [75] and targeting antipsychotic prescription to nursing home residents with dementia [76]; and one doctoral thesis reporting an arts-based intervention for patients with kidney disease [77]. However, some researchers have used the Consensus on Exercise Reporting Template (CERT) [78] to characterize physical activity programs for older adults in Latin America [36], and assess the feasibility of an enhanced prescribed exercise program in older acute medical patients [79] and the effectiveness of falls prevention interventions on reducing falls in hospitalized adults [80].…”
Section: Discussionmentioning
confidence: 99%
“…This framework is appropriate to be applied for those interventions including a number of components interacting with each other, several recipients and outcomes, different skills needed by the facilitators and certain level of tailoring. During the intervention development process, decisions were taken in accordance with evidence from resembling interventions delivered to frail older people, and results from our previous studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]62]. We also integrated the recommendations of a working group, the appropriateness of different frameworks used in implementation research, and evidence shown by few strategies which seemed to be effective.…”
Section: Methodsmentioning
confidence: 99%